The Influence of Live Streaming, Flash Sale, and Free Shipping Programs on Generation Z’s Impulsive Buying with Positive Emotion as the Role of Meditating - Aqsa, Daffa Fernanda; Rosnani, Titik; Pebrianti, Wenny; Ramadania; Heriyadi (Yayasan Sinergi Kawula Muda, 2025)
The rapid growth of e-commerce has revolutionized consumer behavior, especially among Generation Z. who are highly engaged with digital platforms and interactive shopping experiences. This study examines the influence of live streaming, flash sales, and free shipping programs on impulsive buying behavior, with positive emotion serving as a meditating factor. Using data acquired from 326 Generation Z consumers through an online questionnaire, the research used Structural Equation Modeling (SEM) to investigate the correlations between these variables. The findings reveal that all three marketing strategies—live streaming, flash sales, and free shipping—significantly influence impulsive buying. Positive emotion plays a critical meditating role, enhancing the effect of these strategies on spontaneous purchases. Live streaming was found to be the most influential, generating strong emotional responses that drive impulsive buying, followed by flash sales and free shipping. These results offer valuable insights for e-commerce retailers aiming to engage Generation Z through emotionally driven marketing strategies. The study underscores the importance of leveraging positive emotional triggers to increase consumer engagement and impulsive buying behavior in the digital marketplace.